Pengaruh Real Earnings Management dan Corporate Governance Terhadap Corporate Environmental Disclosure - Lia Resti Pratiwi; Kurniawan Kurniawan (STATERA: Jurnal Akuntansi dan Keuangan, 2020)
This study aims to examine real earnings management and corporate governance on corporate environmental disclosure. Real earnings management variables using the approach of Stubben (2010). This study uses 10 companies in the 2014-2017 period. The sample selection method uses non probability sampling method with purposive sampling technique. Data were analyzed using the classic assumption test, descriptive statistics, and moderate regression analysis using SPSS 24. The results of this study prove that real earnings management and corporate governance with a number of boards of commissioners no effect to corporate environmental disclosure., while the board of commissioners and the relationship of independent commissioners effect to corporate environmental disclosure.